(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
Asilah is one of the most important coastal cities in the north-west. It is one of the oldest historical cities in Morocco. It is one of the oldest fortified cities in the north-west on the Atlantic coast ،The "Aladaresa" established the "Asilah" and coincided with the establishment of the city، "Basra "in the year 229 AH، and the date of the establishment of the city in 1900 BC. ، And there is a clear inconsistency in the writing of the name of the city "authentic" among the sources، And the city contains important urban centers (including the fence and doors and the palace and cemeteries)، and politically there was a clear conflict between the sources and the guardian of the city of the original brothers of Mohammed bin Idris، Qasim bin Idris، And the city of Asilah economic and commercial importance is clear ’The tribes of (Luata and Kataamah) played a role in the establishment of this city، and the inhabitants of the city of Asila drinking water on the fresh wells. It is noticeable that the inhabitants of the city of Asilah lack wood because of the distance of the city from the mountainsThe city’s residents import coal from the city of Larache.